A rare case of PSA-negative metastasized prostate cancer to the stomach with serum CEA and CA19-9 elevation: a case report - Koji Shindo; Kenoki Ohuchida; Taiki Moriyama; Fumio Kinoshita; Yutaka Koga; Yoshinao Oda; Masatoshi Eto; Masafumi Nakamura (Surgical Case Reports, 2020)
Abstract Background Metastatic cancer to the stomach is relatively rare. Prostate-specific antigen (PSA) is a reliable biomarker used in the screening and management of patients with prostate cancer. However, it is difficult to definitively diagnose a PSA-negative metastatic gastric tumor of prostate cancer because the cancer sometimes resembles primary gastric cancer in clinical images. It is also difficult to distinguish metastatic cancer from primary cancer even in the pathological examination of biopsy samples when the lesion is poorly differentiated adenocarcinoma. There is a possibility that the characteristics of the cancer are changed during treatment such as chemotherapy or radiation therapy. Therefore, careful consideration is required for surgical indication. Case presentation A 60-year-old male underwent radical prostatectomy and subsequent radiation therapy for advanced prostate cancer (pT3N1M0) 10 years previously, and hormone therapy was started for metachronous multiple bone metastasis 10 months before. Upper gastrointestinal endoscopy revealed an irregular depressed lesion with a convergence of folds at the greater curvature of the upper gastric body. Biopsy showed poorly differentiated adenocarcinoma that was negative for PSA upon immunohistochemistry. He had high serum carcinoembryonic antigen (CEA) (946.1 ng/ml) and carbohydrate antigen 19-9 (CA19-9) (465.1 U/ml) levels with no elevation of PSA (0.152 ng/ml). The tumor was diagnosed as primary gastric cancer based on the clinical imaging and pathological examination of the biopsy sample including the PSA staining. Based on the diagnosis, laparoscopic proximal gastrectomy with lymphadenectomy was performed. However, pathological examination of the resected specimen revealed poorly differentiated adenocarcinoma that was positive for other prostate markers such as androgen receptor. Thus, the patient was diagnosed with metastasized prostate cancer to the stomach. Conclusions We report a case of metastatic gastric cancer of prostate cancer 10 years after radical prostatectomy. In the present case, it was difficult to diagnose a metastatic gastric tumor of prostate cancer preoperatively, because of its resemblance to primary gastric cancer without PSA expression and no serum PSA elevation. Although a rare case entity, it is important to consider the possibility of a metastatic gastric tumor when the surgical indication is determined in cases with another co-existing cancer.